Differentiation of Modernization Processes in EU Countries and in Poland in Time and Space - Non Classical View - Edyta Dworak; Anna Malarska (Comparative Economic Research. Central and Eastern Europe, 2009)
The aim of this paper is a typology of EU-countries from the point of view of their modernization measures, a diagnostics and an evaluation of changes in a sectoral structure of the employment in EU-countries. Against this background there are exposed changes in Polish economy in the period 1997-2008. There were used the multidimensional comparative analysis of the sequence separation of homogenous objects subsets (cluster analysis and quick cluster) and the little known in Poland, but popular in the US, measurement technique of sectoral changes in time - the shift share-technique to illustrate and verify empirically the theory of three sectors by A. Fisher, C. Clark i J. Fourastie\`, orientated to the evaluation of the modernization process of EU-economies.
Keywords: 330